Numerical simulation on truncated oval-nosed projectile penetrating into stiffened plate - Benting ZHU; Guomin WU (Zhongguo Jianchuan Yanjiu, 2022)
ObjectivesIn this paper, the numerical simulation method is used to study the anti-penetration performance and energy absorption mode of a stiffened plate, as well as the influence of different stiffened bars on the flight attitude of the projectile body.Methods Finite element software LS-DYNA is used to simulate the process of a truncated oval-nosed projectile penetrating a stiffened plate, and the results of the numerical simulation are compared with an experiment to verify the reliability of the numerical simulation method. The momentum method and mass equivalence method are used to predict the residual velocity of the projectile, and the applicability of different theoretical methods within different velocity ranges is compared. The deformation energy of different regions of the stiffened plate is then extracted to analyze the influence of the initial velocity of the projectile body on the energy absorption mode of the target plate. Finally, the structure of the stiffeners is changed and the influence of the relative position of the stiffeners on the penetration attitude of the projectile body is analyzed.ResultsThe results show that the mass equivalence method is more accurate than the momentum method in predicting the residual velocity of the stiffened plate when the initial velocity of the projectile body is in the range of 300–900 m/s. The ratio of the deformation energy of the stiffened plate to the energy loss of the projectile body decreases with the increase of the initial velocity of the projectile body. The effect of a T-stiffened plate on trajectory is greater than that of a rectangular-stiffened plate.ConclusionsThe related calculation method and research results have certain reference value for research and engineering application surrounding the anti-penetration of stiffened plates.